The force-temperature relationship in healthy and dystrophic mouse diaphragm; implications for translational study design - Murray, Jason D.; Canan, Ben D.; Martin, Christopher D.; Stangland, Jenna E.; Rastogi, Neha; Rafael-Fortney, Jill A.; Janssen, Paul M. (Frontiers in Physiology, 2012)
In the field of muscular dystrophy, striated muscle function is often assessed in vitro in dystrophin-deficient mdx mice in order to test the impact of a potential treatment strategy. Although many past studies have assessed diaphragm contractile function at or near room temperature, the diaphragm performs in vivo at 37ºC. To improve translation of bench-top results to possible clinical application, we studied temperature-dependence of contractile performance in wild-type (C57BL/10) and mdx muscle strips at temperatures from 25 to 37ºC. Maximal tetanic force in wild-type muscles was higher at 37 ºC (198±11 vs. 155±9 mN/mm2 at 25ºC), while the difference between wild-type and mdx was extremely similar: wild-type muscles produced 45.9% and 45.1% more force at 25 and 37ºC respectively. At 37ºC twitch contraction kinetics and 50% rise time to tetanic plateau were slower in mdx diaphragm. A fatigue/injury protocol indicated two-fold fatigue/contraction induced force deficit in mdx muscles. We conclude that assessment of diaphragm muscle strips can be reliably and reproducibly performed at 37 ºC.